Borderline personality disorder for dummies - Elliott, Charles H., frey50; Smith, Laura L. (Hoboken, NJ : Wiley Pub., 2009)
The sympathetic and comprehensive information presented in this book helps those diagnosed with BPD to get to the root of their condition, develop strategies for breaking the destructive cycle and ultimately learn to live well.
Mapping the boundaries of Borderline Personality Disorder. Exploring Borderline Personality Disorder ; Defining personality to understand BPD ; Describing BPD ; Who gets BPD and why? -- Taking note of the major BPD symptoms. Sensation seeking and self-harm : the impulsivity of BPD ; Explosive feelings and moods ; Missing persons : identity problems and BPD ; Perceiving, understanding, and relating to others ; BPD and extreme thinking ; Slipping away from reality -- Making the choice to change. Preparing to conquer BPD ; Breaking through barriers to change ; Explaining BPD to others ; Taking care of yourself -- Treatments for BPD. Inhibiting impulsivity ; Calming the storms within ; Creating an identity ; Putting yourself in other people's shoes ; Finding shades of gray : changing problematic core beliefs ; Considering medication for BPD -- Advice for people who care. What to do when your partner has BPD ; Befriending people with BPD ; Parenting children at risk for BPD ; Advice for adult children of BPD parents ; Advice for therapists of people with BPD -- The part of tens. Ten quick ways to settle down ; Ten ways to say you're sorry ; Ten things you shouldn't do.
Keywords: Borderline personality disorder; Borderline personality disorder -- Treatment